First calculation of the implementable solar photovoltaic potential in Somogy county and its impact on CO2 emission reduction and job creation - Rodríguez-Segura, Francisco Javier; Osorio-Aravena, Juan Carlos; Muñoz-Cerón, Emilio (JOURNAL OF LANDSCAPE ECOLOGY, 2023)
Due to the current climate urgency, it is necessary to accelerate an energy transition towards renewable energies. To this end, the European Union has set ambitious energy targets. However, in member countries such as Hungary, nuclear energy and fossil fuels continue playing a major role in the energy mix. Nevertheless, this country has a large solar photovoltaic (PV) potential that is hardly exploited, especially in the southern counties, and its technical potential has been less analysed. With the aim to estimate the short-term implementable solar PV potential in Somogy county in southern Hungary, a multi-criteria spatial approach which integrates environmental, technical (with economic attributes), and geographical (with social-acceptability attributes) GIS-based constraints with existing local power plant considerations was employed. Results show that Somogy has a short-term implementable solar PV potential of 2.7 GWp This power potential is about 25 times more than the current installed capacity for generating electricity in Somogy and represents 45% of the national target by 2030 for installed solar PV capacity in Hungary. Furthermore, this potential could create almost 35,000 direct jobs and avoid the emissions of 1.16–2.65 MtCO2 to the atmosphere. The findings and future studies suggested in this work are significant for both local and national levels and could contribute with insights on how to meet climate targets and accelerate energy independence with socio-economic benefits.
Keywords: renewable energy potential; energy transition; Hungary; solar PV